Malaysian development plan system: issues and problems one decade after its reform (2001-2011) - Ahmad, Faizah; Mohd , Ibrahim; Maidin, Syra Lawrance; Zainol, Rosilawati; Mohd. Noor, Norzailawati (Malaysian Institute of Planners, 2013)
In 2001 the Town and Country Planning Act 1976 (Act 172) was amended through Act A1129). The amendments included provisions to allow four levels of government involvement (Federal, Regional, State and Local Authority) in spatial planning, with the intention of establishing a more effective development plan system in Malaysia. However, an assessment of the relationship between legislative provision and the implementation of development planning is urgently required to consider a number of issues, including delays in adopting plans and the continued existence of out of date plans. Therefore, this paper discusses issues and problems encountered by selected local planning authorities in the implementation of the development planning system. The discussion focuses on the capacity and capability of these authorities with regard to legal aspects, administration, finance, human resource issuess and technical support. The data were obtained through mixed methods i.e. postal surveys, interviews with representatives from selected local authorities and focus group discussions with selected professional town planners. The findings demonstrate that most of the issues and problems encountered in implementing the development plan system at each plan level in Malaysia are legal in origin.